Nitrogen Addition and Understory Removal but Not Soil Warming Increased Radial Growth of Pinus cembra at Treeline in the Central Austrian Alps - Gruber, Andreas; Oberhuber, Walter; Wieser, Gerhard (Frontiers in Plant Science, 2018)
Beside low temperatures, limited tree growth at the alpine treeline may also be attributed to a lack of available soil nutrients Beside low temperatures, limited tree growth at the alpine treeline may also be attributed to a lack of available soil nutrients and competition with understory vegetation. Although intra-annual stem growth of Pinus cembra has been studied intensively at the alpine treeline, the responses of radial growth to soil warming, soil fertilization, and below ground competition awaits clarification. In this study we quantified the effects of nitrogen (N) fertilization, soil warming, and understory removal on stem radial growth of P. cembra at treeline. Soil warming was achieved by roofing the forest floor with a transparent polyvinyl skin, while understory competition was prevented by shading the forest floor with a non-transparent foil around six trees each. Six trees received N- fertilization and six other trees served as controls. Stem growth was monitored with band dendrometers during the growing seasons 2012-2014. Our three year experiment showed that soil warming had no considerable effect on radial growth. Though understory removal through shading was accompanied by root-zone cooling, understory removal as well as N fertilization led to a significant increase in radial growth. Hardly affected was tree root biomass, while N-fertilization and understory removal significantly increased in 100-needle surface area and 100-needle dry mass, implying a higher amount of N stored in needles. Overall, our results demonstrate that beside low temperatures, tree growth at cold-climate boundaries may also be limited by root competition for nutrients between trees and understory vegetation. We conclude that tree understory interactions may also control treeline dynamics in a future changing environment.